Antifungal Constituents from the Roots of Piper dilatatum Rich. - Ruilan Alves dos Santos; Clécio Souza Ramos; Maria Cláudia M. Young; Thamilles Gonçalves Pinheiro; André M. Amorim; Massuo J. Kato; Ronan Batista (Journal of Chemistry)
The compounds (+)-(7S,8R)-epoxy-5,6-didehydrokavain (1), flavokavain B (2), β-sitosterol (3), and stigmasterol (4) are reported here as chemical constituents of Piper dilatatum Rich. (Piperaceae). Their structures were determined on the basis of their spectroscopic data (1H and 13C NMR, MS, and IR). The antifungal activities of pyrone 1 (1 μg) and chalcone 2 (100 μg) were determined by means of direct bioautography against Cladosporium cladosporioides and C. sphaerospermum. Results indicate P. dilatatum as a candidate for the development of novel antifungal phytotherapic products as well as point out pyrone 1 as a promising hit compound in the quest for novel antifungal agents.